Belgium : Selected Issues-Regional Labor Markets in Belgium. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper analyzes the regional labor markets for Belgium. The paper examines labor market performance, and argues that a number of factors-poor worker-job matching, a compressed wage structure, and low geographical mobility-contribute to economic disparities. The paper describes the divergences in local labor markets, and offers potential explanations for them, including an analysis of variations in the relationship between regional unemployment rates and regional vacancy rates. The paper also describes how labor markets adjust in Belgium and in its two main regions.